Fenomena FYP TIKTOK Terhadap Pembentukan Identitas Remaja - Ahmad Arkham; Adinus Saifur Rizal; Muhammad Irfan Fauzan; Khairil Fathani (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The phenomenon of TikTok’s FYP (For You Page) in shaping adolescent identity is a complex and multifaceted topic, depending on the context of each individual involved. Social media, particularly the FYP (For You Page) on TikTok, can have positive influences when used within reasonable limits, as it can strengthen identity and empower individuals by allowing them to express their values, interests, and beliefs, as well as increase self-confidence through sharing experiences. However, social media—especially the FYP—also triggers social comparison, creating pressure to conform to certain standards of beauty, lifestyle, or achievement. This can influence how adolescents perceive themselves, and may even encourage them to alter their character and appearance in order to follow trending standards. This study employs a descriptive qualitative method using Erik Erikson’s identity theory. This approach provides broader insights into the influence of social media on adolescent identity in the digital era.